Impact of climate change on occupational health and productivity: a systematic literature review focusing on workplace heat - Levi, Miriam; Kjellstrom, Tord; Baldasseroni, Alberto (La Medicina del Lavoro, 2018)
Background: With climate change, mean annual air temperatures are getting hotter and extreme weather events will become more and more common in most parts of the world. Objectives: As part of the EU funded project HEAT-SHIELD we conducted a systematic review to summarize the epidemiological evidence of the effects of global warming-related heat exposure on workers’ health and productivity. Methods: Three separate searches, focused, respectively, on: i) heat-related illness (HRI), cardiovascular, respiratory and kidney diseases; ii) traumatic injuries; and iii) vector-borne diseases or vectors distribution, were conducted in PubMed. EMBASE was also consulted to retrieve relevant studies focused on the health effects of climate change. A fourth search strategy to assess the effects on work productivity was conducted both in PubMed and in the SCOPUS database. Results: A significant proportion of studies reported findings regarding the Mesoamerican nephropathy issue. This is a disease occurring especially among young and middle-aged male sugarcane workers, without conventional risk factors for chronic kidney disease. For injuries, there is a reversed U-shaped exposure-response relationship between Tmax and overall daily injury claims. Outdoor workers are at increased risk of vector-borne infectious diseases, as a positive correlation between higher air temperatures and current or future expansion of the habitat of vectors is being observed. As for productivity, agriculture and construction are the most studied sectors; a day with temperatures exceeding 32°C can reduce daily labour supply in exposed sectors by up to 14%. Conclusions: The present findings should inform development of further research and related health policies in the EU and beyond with regard to protecting working people from the effects of workplace heat during climate change.